METABOLIC CHANGES OF CONNECTIVE TISSUE IN CHILDREN WITH BONE CYST - O. M. Magomedov; A. F. Levytsky; D. V. Golovatiuk; A. N. Velikyy; T. A. Polishchuk (Biotechnologia Acta, 2013)
The results of the study of diagnostically important metabolism parameters in patients with bone cysts in different stages of the disease are presented. It is shown that an increase activity of protein banding collagenase, alkaline phosphatase and also of hydroxyproline, glycosaminoglycans contents due to lower levels of calcium and inorganic phosphate levels increase in blood serum are expressed in a stage osteolysis than the step of separating. Decreasing the amount of glycosaminoglycans and collagen in bone indicates an intensification of catabolic processes in the connective tissue matrix.